Rapid diagnostic tests for typhoid and paratyphoid (enteric) fever - Wijedoru, L; Mallett, S; Parry, CM (Cochrane Collaboration, 2017)
Background: Differentiating both typhoid (Salmonella Typhi) and paratyphoid (Salmonella Paratyphi A) infection from other causes of fever in endemic areas is a diagnostic challenge. Although commercial point‐of‐care rapid diagnostic tests (RDTs) for enteric fever are available as alternatives to the current reference standard test of blood or bone marrow culture, or to the widely used Widal Test, their diagnostic accuracy is unclear. If accurate, they could potentially replace blood culture as the World Health Organization (WHO)‐recommended main diagnostic test for enteric fever.